Typical visual unfamiliar face individuation in left and right mesial temporal epilepsy. (October 2020) - Volfart, Angélique; Jonas, Jacques; Maillard, Louis; Busigny, Thomas; Rossion, Bruno; Brissart, Hélène
Abstract: Patients with chronic mesial temporal lobe epilepsy have difficulties at identifying familiar faces as well as at explicit old/new face recognition tasks. However, the extent to which these difficulties can be attributed to visual individuation of faces, independently of general explicit learning and semantic memory processes, is unknown. We tested 42 mesial temporal lobe epilepsy patients divided into two groups according to the side of epilepsy (left and right) and 42 matched controls on an extensive series of individuation tasks of unfamiliar faces and control visual stimuli, as well as on face detection, famous face recognition and naming, and face and non-face learning. Overall, both patient groups had difficulties at identifying and naming famous faces, and at explicitly learning face and non-face images. However, there was no group difference in accuracy between patients and controls at the two most widely used neuropsychological tests assessing visual individuation of unfamiliar faces (Benton Facial Recognition Test and Cambridge Face Memory Test) . While patients with right mesial temporal lobe epilepsy were slowed down at all tasks, this effect was not specific to faces or even high-level stimuli. Importantly, both groups showed the same profile of response as typical participants across various stimulus manipulations, showing no evidence of qualitative processing impairments. Overall, these results point to largely preserved visual face individuation processes in patients with mesial temporal lobe epilepsy, with semantic and episodic memory difficulties being consistent with the localization of the neural structures involved in their epilepsy (anterior temporal cortex and hippocampus). These observations have implications for the prediction of neuropsychological outcomes in the case of surgery and support the validity of intracranial electroencephalographic recordings performed in this population to understand neural mechanisms of human face individuation, notably through intracranial electrophysiological recordings and stimulations. Highlights: A range of face recognition tasks is tested in a group of MTLE patients and controls. MTLE have difficulties recognizing famous faces and learning visual stimuli. Individuation of unfamiliar faces is quantitatively and qualitatively preserved in MTLE. Right MTLE patients are slowed down at all explicit tasks due to general factors.